Management Model of Character Education Based Whole School Development Approach: A Research and Development - Marnayana Marnayana; Muhammad Zuhri Abu Nawas; Baderiah Baderiah; Muhammad Guntur (STAI Hubbulwathan Duri, 2024)
One aspect that has yet to receive much attention in the era of Education 4.0 is character education for students. For this reason, innovation is needed in developing a character education management model based on the whole school development approach. This study aims to develop a model of character education management for vocational school students. Using an RD design, this study involved teachers at vocational schools and validators in Palopo City, South Sulawesi, Indonesia. Data were collected using questionnaires, interviews, validation sheets, and observation sheets and were analyzed qualitatively and quantitatively. The study results show that the whole school development approach-based character education management model is valid, practical, and effective in developing student character. With these findings, it is hoped that vocational school teachers can develop a character education management model according to the needs of their respective schools so as to develop into better individuals in all aspects of life.